DETERMINATION OF MINIMAL INHIBITING CONCENTRATIONS OF BEDAQUILINE FOR DRUG SUSCEPTIBILITY TESTING - I. V. Peretokina; L. Yu. Krylova; Yu. D. Mikhaylova; S. G. Safonova; M. V. Makarova (Туберкулез и болезни лёгких)
.